Sedimentary and foraminiferal records of Late Quaternary environmental change west of Ireland and implications for the last British–Irish Ice Sheet. (6th May 2020) - Peters, Jared L.; Benetti, Sara; Dunlop, Paul; Wheeler, Andrew J.
ABSTRACT: Palaeoenvironmental change following deglaciation of the last British–Irish Ice Sheet on the continental shelf west of Ireland was investigated using multiproxy analyses of sediment and foraminifera data from nine sediment cores. Lithofacies associations record various depositional regimes across the shelf, which evolve from subglacial to postglacial conditions. Census data provide the first characterisation of benthic foraminifera populations across the continental shelf and multivariate analyses reveal three distinct biotopes. Biomineralization within these biotopes is restricted to ≤21 200 cal a bp by four radiocarbon ages. The transition from glacial to postglacial benthic foraminifera populations near the shelf break marks the establishment of productive, nutrient‐rich, ice‐distal conditions at ~20 900 cal a bp ; these conditions may also mark the start of favourable conditions for postglacial cold‐water coral growth. Postglacial conditions on the inner shelf were not established until <14 500 cal a bp, suggesting glacial conditions west of Ireland may have persisted into the Bølling–Allerød Interstadial.